2020
DOI: 10.3892/etm.2020.9245
|View full text |Cite
|
Sign up to set email alerts
|

Irbesartan ameliorates myocardial fibrosis in diabetic cardiomyopathy rats by inhibiting the TGFβ1/Smad2/3 pathway

Abstract: Myocardial fibrosis (MF) is an important pathological change in diabetic cardiomyopathy. The aim of the present study was to investigate whether irbesartan serves a role in improving MF in a diabetic rat model. Fasting blood glucose (FBG), total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C) levels were measured in rats using biochemical methods. Heart weight index (HWI), left ventricular weight index (LVWI), left ventricular sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…EXE and MET were able to reduce the levels of LDL, which carry blood cholesterol, and thus make an important contribution to the prevention of cardiovascular pathologies in terms of lipid regulation. Consistent with these results, Zong et al obtained similar HDL and LDL results in their DM-2 rat model [ 30 ]. Furthermore, Baretti et al showed that obese rat LDL levels decreased by 61% with EXE [ 31 ].…”
Section: Discussionsupporting
confidence: 72%
“…EXE and MET were able to reduce the levels of LDL, which carry blood cholesterol, and thus make an important contribution to the prevention of cardiovascular pathologies in terms of lipid regulation. Consistent with these results, Zong et al obtained similar HDL and LDL results in their DM-2 rat model [ 30 ]. Furthermore, Baretti et al showed that obese rat LDL levels decreased by 61% with EXE [ 31 ].…”
Section: Discussionsupporting
confidence: 72%
“…Irbesartan ameliorates myocardial fibrosis in diabetic cardiomyopathy ( 15 ). It is an angiotensin domain receptor inhibitor and is considered to be a common medication for improving the structure and function of cardiomyocytes and reducing the risk of death from heart failure ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…The specific deletion of Tgfbr1/2 and Smad3 notably reduce cardiac fibrosis resulting from transverse coarctation of aorta, and Smad3 is activated downstream of TGF-b receptor (166,167). In vivo drug research found that inhibiting TGF-b/Smad2/3 pathway can inhibit the proliferation and collagen production of CFs and attenuate the degree of cardiac fibrosis (168). In recent years, there are several researches focus on how TGF-b signaling pathway regulates the phenotypic transformation and function of CFs.…”
Section: Advanced Glycation End Products Affect Cardiac Fibroblastsmentioning
confidence: 99%
“…But it is encouraging that the related research is increasing year by year (188). Previous studies have shown that Irbesartan inhibits CFs proliferation and ameliorates myocardial fibrosis in T2DM rats (168). Inhibition of SGLT1 expression in CFs improves DCM cardiac fibrosis by attenuating myofibroblasts activation (90), and the SGLT1/2 inhibitor sogliflozin (zynquista) has completed phase III clinical trials (189), suggesting a novel therapeutic strategy for the treatment of DCM fibrosis.…”
Section: Future Perspectivementioning
confidence: 99%